Candi Ngempon sebagai Daya Tarik Wisata Edukasi dan di Kabupaten Semarang - Avandi Okta Syahputra; Aurilia Triani Aryaningtyas (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2024)
Ngempon Temple is one of the historical sites that have the potential to become an educational and historical tourist attraction in Ngempon Village, Bergas District, Semarang Regency, Central Java. This study aims to identify the potential and challenges of managing Ngempon Temple as an educational tourist attraction. Using a qualitative approach with the Miles and Huberman data analysis method, this study involved interviews with tourists, managers, and local communities as key informants. The results of the study indicate that although Ngempon Temple has high historical value and is an attraction for educational tourists, several challenges are still faced, such as limited promotion, inadequate facilities, and minimal delivery of historical information, limiting the optimization of educational tourism potential. To overcome these challenges, innovative strategies are needed, including using digital technology and increasing community participation in management. This study provides important implications for developing other historical tourist attractions in Indonesia. It also emphasizes better integration between government, society, and technology.